Digital Literacy Integrated with Blended Learning in Improving EFL Students’ English Language Skills: A Lesson Learned from the Independent Campus Program - Wahyuddin, Nur Rahmah; Yanti, Nur Eva; Arnas, Riska; Hermansyah, Sam (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2024)
The integration of digital literacy into educational practices has garnered significant attention in recent years, particularly in the context of language learning. Digital literacy refers to the ability to effectively and critically navigate, evaluate, and create information using various digital technologies. Given its growing importance, this study sought to evaluate the impact of digital literacy competence on improving English language skills through blended learning in the Independent Campus Program at Ichsan Sidenreng Rappang University. Employing a quantitative experimental method with a one-group pretest-posttest design, the study gathered data through English language tests and questionnaires. The results demonstrated a significant improvement in students’ English skills, with the pretest average score of 31.7 rising to 84.7 in the posttest. The Paired Sample t-test confirmed the statistical significance of this difference (p-value = 0.000). Additionally, the Pearson correlation test revealed a moderate positive relationship between digital literacy and English proficiency (r = 0.456), indicating that students with higher digital literacy competencies tended to perform better in English. These findings underscore the significant role that digital literacy plays in enhancing language skills, particularly when integrated with technology-based learning approaches. For future research, further studies could explore the long-term impact of digital literacy on language acquisition, the effectiveness of various digital tools in language learning, and how digital literacy interacts with other factors, such as motivation and learning styles, to influence language proficiency. Additionally, expanding the research to include diverse educational settings and student populations could provide a broader understanding of digital literacy’s role in language education.